Prevalence and Anatomical Distribution of Paranasal Sinus Osteomas: A Retrospective Analysis - Salih, Mahabad Abdalaziz (Journal of Sulaimani Medical College, 2025)
Background and Objectives: Paranasal sinus osteomas (PSOs) are benign bony tumors with variable prevalence across different populations. This study aimed to assess the prevalence, anatomical distribution, and complications of PSOs in a contemporary Iraqi cohort. Methods: This retrospective study was conducted at a tertiary medical center in Sulaymaniyah, Iraq, between March 2023 and September 2024. Computed tomography (CT) scans of 520 adult patients who underwent sinonasal imaging were reviewed. Two board-certified radiologists independently evaluated the presence, size, and location of osteomas. Descriptive analysis and 95% confidence intervals (CIs) were applied. Results: Osteomas were identified in 16 out of 520 patients, yielding a prevalence of 3.5% (95% CI: 2.0–5.0%). The mean age of affected patients was 38.55 ± 13.93 years. The most commonly involved sites were the left ethmoidal and right frontal sinuses (each 25%), followed by the left frontal and right ethmoidal sinuses (each 18.75%). One patient (6.25%) experienced a complication—sinusitis. Conclusion: This study demonstrates a PSO prevalence consistent with global estimates. The majority of osteomas were located in the ethmoid and frontal sinuses and were asymptomatic, reinforcing the role of radiologic evaluation in sinonasal assessments.
Keywords: Paranasal sinuses; Computed Tomography; Osteoma; sinusitis; Prevalence